2010
DOI: 10.1016/j.fct.2009.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective potential of emulsions formulated with Buriti oil (Mauritia flexuosa) against UV irradiation on keratinocytes and fibroblasts cell lines

Abstract: Considering the belief that natural lipids and edible substances are safer for topical applications and that carotenoids are able to protect cells against photooxidative damage, wea have investigated whether topical creams and lotions, produced with Buriti oil and commercial surfactants, can exert photoprotective effect of against UVA and UVB irradiation. Emulsions and plain Buriti oil were diluted in DMEM medium supplemented with 10% FBS. Cell treatment was divided in two stages, prior and after being exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
16

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 41 publications
1
33
0
16
Order By: Relevance
“…The in vitro antibacterial and healing activity of buriti oil was performed by Batista et al [58], with greater sensitivity to buriti oil in B. subtilis, K. pneumoniae and S. aureus and the healing activity assay in the Fourteenth day in the oil-treated group, a significant reduction in macrophage counts was observed and a significant increase in fibroblast and collagen fibre. The results allowed us to conclude that buriti oil (M. flexuosa) showed antibacterial activity in vitro in both gram-positive and gram-negative bacteria and was efficient in the healing process of skin wounds in Wistar rats, since it promoted a Good result in the group treated with buriti oil in relation to the control group [70,71].…”
Section: Buriti Oil In Wound Healingmentioning
confidence: 88%
“…The in vitro antibacterial and healing activity of buriti oil was performed by Batista et al [58], with greater sensitivity to buriti oil in B. subtilis, K. pneumoniae and S. aureus and the healing activity assay in the Fourteenth day in the oil-treated group, a significant reduction in macrophage counts was observed and a significant increase in fibroblast and collagen fibre. The results allowed us to conclude that buriti oil (M. flexuosa) showed antibacterial activity in vitro in both gram-positive and gram-negative bacteria and was efficient in the healing process of skin wounds in Wistar rats, since it promoted a Good result in the group treated with buriti oil in relation to the control group [70,71].…”
Section: Buriti Oil In Wound Healingmentioning
confidence: 88%
“…Dados reportam que, quando usado em produtos pós-sol, o óleo de buriti evita danos provocados por radiação UV, justamente por apresentar propriedades fotoprotetoras (ZANATTA et al, 2010). A quantidade de óleo empregada varia de acordo com a finalidade do produto a ser formulado.…”
Section: )unclassified
“…O uso de antioxidantes, como flavonoides, por exemplo, compostos comumente encontrados em vegetais com a função de protegê-los contra radiação UV, poderia apresentar papel sinérgico e complementar os filtros solares, atuando na proteção solar (8,(14)(15)(16)(17). Alguns estudos já demonstraram evidências favoráveis com relação ao uso de óleos e extratos vegetais em formulações voltadas à proteção solar (8,17,18). Tendo em vista a Biodiversidade Brasileira, algumas espécies, apesar de já apresentarem utilização em cosméticos, necessitam de estudos complementares sobre suas potenciais atividades antioxidantes e fotoprotetoras.…”
Section: Murumuru (Astrocaryum Murumuru)unclassified
“…A estratégia de investigação de novos compostos envolve potencial ação antioxidante e/ou presença de cromóforos em sua molécula que them against UV radiation, could provide synergistic and complementary role in sunscreens for improved sun protection (8,(14)(15)(16)(17). Some studies have shown favourable evidence regarding the use of oils and plant extracts in formulations aimed at sun protection (8,17,18). In view of the Brazilian biodiversity, some species, although already present in cosmetic use, require further studies of their potential photoprotective and antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%